Technical evaluation on FIQIR road safety from expert's perspective - Norkhairani, Abdul Rawi; Abd.Rasid, Mamat; Mat Atar, Mat Amin (Universiti Teknikal Malaysia Melaka, 2016)
An earlier paper of FIQIR Road Safety had been published in Journal of Technology whilst in this paper; FIQIR is focusing on technical aspects evaluation from the expert’s view. The experts were one from multimedia industry and three academicians from Multimedia School. The feedback from experts collected through a questionnaire set. The questionnaire includes contents, navigation or interactivity, presentation of the prototype and the use of animations as aspects to be observed by selected experts. According to multiple previous studies, they are important criteria to be considered during evaluation of usability. Results obtained shown that ten (10) aspects over fourteen (14) observed by the reviewers were above the average score of 4.00 according to the Likert scale. Further enhancements will be carried out towards the prototype based on the findings of this study.